2012
DOI: 10.1093/jnci/djs451
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of 18FDG-PET-CT Findings in Clinical Stage III and IIB Breast Cancer

Abstract: BackgroundThis study prospectively evaluated the yield of fluorodeoxyglucose positron emission tomography/computed tomography (18FDG-PET-CT) in patients with clinical stages II and III breast cancer and the impact of PET-CT results on prognosis.MethodsIn the course of 71 months, 254 consecutive patients with clinical stages II and III breast cancer (based on clinical examination, mammography, breast magnetic resonance imaging, and locoregional ultrasonography) underwent 18FDG-PET-CT. The yield was assessed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
104
2
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(122 citation statements)
references
References 27 publications
9
104
2
7
Order By: Relevance
“…We observed that extra-axillary lymph nodes were more frequent in patients with grade 3 tumours in comparison with lower grades (29% vs. 13%, P = 0.004) but the rate of distant metastases did not differ (17% vs. 21%, P = 0.418) [11].…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…We observed that extra-axillary lymph nodes were more frequent in patients with grade 3 tumours in comparison with lower grades (29% vs. 13%, P = 0.004) but the rate of distant metastases did not differ (17% vs. 21%, P = 0.418) [11].…”
mentioning
confidence: 57%
“…The larger evaluations have been performed in locally advanced and inflammatory BC [6][7][8] which are usually regarded as equivalent to stage III cancer of the AJCC classification [9]. More recent studies have suggested that PET/CT could also be valuable in stage II patients, especially in stage IIB [2,10,11]. In 254 patients with BC of mixed phenotypes, we detected distant metastases with PET/CT in 2.3% (1/44) of clinical stage IIA, 10.7% (6/56) of stage IIB, 17.5% (11/63) of stage IIIA, 36.5% (27/ 74) of stage IIIB and 47.1% (8/17) of stage IIIC patients [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 Also, an early change in 18 F-FDG uptake is a potential predictive biomarker of response to NAC. [8][9][10][11][12] However, at baseline, as demonstrated in recent studies, ER-positive tumors are usually characterized by rather low standardized uptake values (SUVs) because of lower 18 F-FDG uptake compared with other breast cancer phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, PET/CT is currently used for the staging of stage IIB and stage III locally advanced breast cancer (LABC) [12][13][14][15]. Additional information that can be gained from baseline SUV of the primary tumour can be of interest.…”
mentioning
confidence: 99%